Modulating thermo-mechanical properties of lead-free Sn-30Bi TIM by adding In-3Ag alloy - Munim Shahriar Jawad; Md. Asif Mahmud Noman; Ridwan Radit Ahsan; Md. Muktadir Billah (Journal of Alloys and Metallurgical Systems)
This research work is focused on studying the effect of indium (In) and silver (Ag) addition on the thermo-mechanical properties of lead-free Sn-Bi solder alloy. Sn-30B is a potential solder to be used as thermal interface material; however, its enhanced thermo-mechanical properties are yet to be explored. In this study, authors therefore investigated the effect of In-3Ag alloy addition to tailoring the thermo-mechanical properties of the Sn-30Bi solder alloy. The microstructural evolution with progressive alloying was studied using both optical and field emission scanning electron microscopy (FESEM). Elemental analysis to confirm the alloying was done using the energy dispersive spectroscopy (EDS). Simultaneous thermogravimetry-differential scanning calorimetry (STA/TG-DSC) was used to study the thermal behavior of all the solder alloys. To assess the mechanical properties, microhardness and tensile properties were also measured. Finally, the effect of low-temperature ageing was also studied to evaluate the performance of the newly developed solder alloy as thermal interface material at the operating temperature. From these results, it was found that the Sn-30Bi-3(In-3Ag) alloy has superior properties among all the solder alloys.